Regional Industrial Deconcentration In Brazil (1985 – 1998) - Aurílio Sérgio Costa Caiado (European Regional Science Association (ERSA), 2003)
The paper is based on the statement that in the process of productive deconcentration in Brazil – specially of the industrial one, between 1970 and 1985 – the State actions were structuring, in the sense that it, and not only intensified the productive integration of the national market (1962/1985), but also made possible a larger “soldering” between the movement of the different regional economies and the general movement of the national economy accumulation dynamics. The abandonment of the “developmental State” since mid 80s and, above all, the implantation of the neo - liberal procedures in the 90s have altered the localization patterns of the most dynamic activities. The “Fiscal War”, as a mechanism of (mistaken) defense of regions and settlements became tougher. The end of the “tripod” and the supremacy of the private investment turned the regional localization strongly selective. The deconcentration process was stopped and had even resulted in some concrete manifestations of productive reconcentration. Thus, the decision of investment of the private capital - national or international - started depending on a kind of localization “auction”, that was responsible for the liquid transferring of public resources to private companies, imposing strong selectivity to the regional development. The dynamics of the post-1989 regional economy was no longer a stage of productive integration, as while the integration corresponded to a true process of "opening of the regional borders" for accumulation, the commercial opening and the national market deregulation had the same meaning in international terms. The growth motor was no longer the domestic market but the “integration" to the international economy, what weakened the regional solidarity links and reduced the growth propelling effects. In spite of the distinguished sectoral and regional effects, the dominance became increasingly commanded by the great world oligopolies. The incentive effects on the national productive structure became weaker and the effects of blockage or inhibition and even of destruction were enlarged.
Keywords: 330